The pretty girl killer - Byrne, Andrew (Docklands, VIC : Penguin Random House Australia, 2019)
This is the story of Christopher Wilder: the surf-loving son of a decorated naval war hero born in the suburbs of Sydney, who became the most wanted man in America -- a psychopathic serial killer who slaughtered more than sixteen young women in the USA and is the prime suspect in the infamous Australian Wanda Beach murders. Wilder was handsome and charming, and time and time again he managed to convince beautiful young women that he was a fashion photographer looking to help them start a career in modelling. What followed were some of the most brutal, sadistic crimes the world has ever seen -- as well as a years-long police operation, dogged by missed opportunities and bad decisions, to track the killer down. Featuring new evidence unearthed from case files and interviews with FBI agents, witnesses and survivors, some of whom have spoken for the first time since the horrendous crimes were committed, The Pretty Girl Killer takes us right into the mind and moment of one of Australia's most heinous exports.
Keywords: Wilder, Christopher Bernard, -- 1945-1984 -- Biography; Criminal investigation; Serial murderers -- Biography; Serial murderers -- Case studies; Murder -- Australia -- Case studies; Murder -- United States -- Case studies; Male serial murderers -- Australia; Male serial murderers -- United States; True crime; Australian; Biographies